Information Pursuit in Financial Statement Analysis: Effects of Choice, Effort, and Reconciliation - Nelson, Mark W.; Tayler, William B. (The Accounting Review, 2007)
Prior research provides evidence that information affects financial statement users' judgments less when that information is provided in a less accessible format (e.g., information disclosed in a footnote or less prominent financial statement rather than being recognized on the income statement [Maines and McDaniel 2000]). We provide evidence that, conditional on users performing the analysis necessary to transform the financial statements to appear as if disclosed information had been recognized, that information may affect users' judgments more than it would have if it had been recognized initially. Our experiments are set in the context of constructive capitalization of operating leases. The first experiment manipulates three variables that we hypothesize will contribute to this effect: choice to use transformed financial statements, effort spent on the transformation process, and reconciliation of pre- and post-transformation numbers. We provide evidence that, in the constructive-capitalization setting we operationalize, information has a greater effect on judgments when effort was expended to obtain the information and the information is displayed in a reconciled format. The second experiment focuses on the effort effect and replicates it with additional controls. These results have implications for standard-setters who consider the relative benefits of recognition and disclosure, and for financial statement users who transform financial statements as part of their analyses.